Thermal Performance Comparison of Parabolic Trough Collector (PTC) Using Various Nanofluids - Shirole, Ashutosh; Wagh, Mahesh; Kulkarni, Vivek (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
The objective of this paper is to investigate the theoretical performance of Parabolic Trough Collector (PTC) using various nanofluids. The theoretical performances are calculated for Al2O3, graphite, magnetite, SWCNH, CuO, SiO2, MWCNT, TiO2, Fe2O3, and ZnO in water nanofluids. The heat transfer equations, thermodynamic properties of nanofluid and pumping power are utilised for the development of novel thermal model.Â The theoretical thermal efficiency of the PTC is calculated, and the economic viability of the technology is predicted for a range of nanofluid concentration. The results showed that the thermal conductivity increases with the concentration of nanoparticles in the base fluid. Magnetite nanofluid showed the highest thermal efficiency, followed by CuO, MWCNT, ZnO, SWCNH, TiO2, Fe2O3, Al2O3, graphite, and SiO2, respectively. The study reveals that MWCNT at 0.4% concentration is the best-suited nanofluid considering thermal gain and pumping power. Most of the nanofluids achieved optimum efficiency at 0.4% concentration. The influence of mass flow rate on thermal efficiency is evaluated. When the mass flow rate increased from 70 Kg/hr to 90Kg/hr, a 10%-20% efficiency increase is observed. Dispersing nanofluids reduces the levelized cost of energy of large-scale power plants. These findings add to the knowledge of the scientific community aimed explicitly at solar thermal energy technology. The report can also be used as a base to pursue solar thermal projects on an economic basis.